Negotiating social identity when contexts change maintaining identification and responding to threat - Ethnier, Kathleen A.; Deaux, Kay (1994)
The impact of change in context on identity maintenance, the implications of maintenance efforts for group identification, and the effects of perceived threats to identity on self-esteem associated with group membership are examined in a longitudinal study of Hispanic students during their 1st year at predominately Anglo universities. Whereas ethnic identity is initially linked to the strength of the students' cultural background, maintenance of ethnic identity is accomplished by weakening that link and remooring the identity to the current college context. Results suggest 2 distinct paths by which students negotiate their ethnic identity in a new context. Students with initially strong ethnic identity become involved in cultural activities, increasing the strength of their identification. In contrast, students with initially weaker identification perceive more threat in the environment, show decreases in self-esteem associated with group membership, lowering identification with their ethnic group. The findings both support social identity theory and illustrate the need for more contextual analyses of identity processes.
Includes bibliographical references.
Keywords: Social identity; Ethnic identity